Synthesis and Fluorescence Properties of Asymmetrical Salamo-Type Tetranuclear Zinc(II) Complex - Yun-Dong Peng; Xiao-Yan Li; Quan-Peng Kang; Gao-Xian An; Yang Zhang; Wen-Kui Dong (Crystals, 2018)
A new tetranuclear zinc(II) complex with an asymmetrical Salamo-type chelating ligand, H3L (5-methoxy-6′-hydroxy-2,2′-[ethylenedioxybis(nitrilomethylidyne)]diphenol), was synthesized and characterized using FT-IR, elemental analyses, X-ray single crystal diffraction method, UV-Vis, and fluorescence spectra. The zinc(II) complex possesses the cell parameters a = 8.1960(7) Å, b = 9.8127(8) Å, c = 16.5428(15) Å, Z = 1, V = 1172.5(2) Å3, R1 = 0.0722, and wR2 = 0.1558, and crystallizes in the triclinic system, with space group P-1. X-ray crystal structure analysis reveals that Zn1 and Zn2 atoms are all pentacoordinated and adopt slightly twisted tetragonal pyramidal and trigonal bipyramidal geometries. The zinc(II) complex forms a 1D supramolecular chain via intermolecular hydrogen bonds along the b axis. Besides, the fluorescence properties have been discussed.